Using mathematics to understand the world : how culture promotes children's mathematics - Nunes, Terezinha; Bryant, Peter, 1937- (London : Routledge, 2022)
"Using Mathematics to Understand the World: How culture promotes children's mathematics offers fundamental insight into how mathematics permeates our lives as a way of representing and thinking about the world. Internationally renowned experts Terezinha Nunes and Peter Bryant examine research into children's mathematical development to show why it is important to distinguish between quantities, relations and numbers. Using Mathematics to Understand the World presents a theory about the development of children's quantitative reasoning and reveals why and how teaching about quantitative reasoning can be used to improve children's mathematical attainment in school. It describes how learning about the analytical meaning of numbers is established as part of mathematics at school but quantitative reasoning is emphasized less even though it is increasingly acclaimed as essential for thinking mathematically and for using mathematics to understand the world. This essential text is for all students of mathematics education, developmental psychology and cognitive psychology. By including activities for parents and professionals to try themselves, it may help you to recognize your own quantitative reasoning"--
Includes bibliographical references and indexes.
Keywords: Reasoning -- Study and teaching (Primary); Reasoning -- Study and teaching (Secondary); Mathematics -- Study and teaching (Primary); Mathematics -- Study and teaching (Secondary); Reasoning in children